Genetic Structure of and Evidence for Admixture between Western and Korean Native Pig Breeds Revealed by Single Nucleotide Polymorphisms - Edea, Zewdu (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2014)
Comprehensive information on genetic diversity and introgression is desirable for the design of rational breed improvement and conservation programs. Despite the concerns regarding the genetic introgression of Western pig breeds into the gene pool of the Korean native pig (KNP), the level of this admixture has not yet been quantified. In the present study, we genotyped 93 animals, representing four Western pig breeds and KNP, using the porcine SNP 60K BeadChip to assess their genetic diversity and to estimate the level of admixture among the breeds. Expected heterozygosity was the lowest in Berkshire (0.31) and highest in Landrace (0.42). Population differentiation (F(ST)) estimates were significantly different (p<0.000), accounting for 27% of the variability among the breeds. The evidence of inbreeding observed in KNP (0.029) and Yorkshire (0.031) may result in deficient heterozygosity. Principal components one (PC1) and two (PC2) explained approximately 35.06% and 25.20% of the variation, respectively, and placed KNP somewhat proximal to the Western pig breeds (Berkshire and Landrace). When K = 2, KNP shared a substantial proportion of ancestry with Western breeds. Similarly, when K = 3, over 86% of the KNP individuals were in the same cluster with Berkshire and Landrace. The linkage disquilbrium (LD) values at r(2) (0.3), the physical distance at which LD decays below a threshold of 0.3, ranged from 72.40 kb in Landrace to 85.86 kb in Yorkshire. Based on our structure analysis, a substantial level of admixture between Western and Korean native pig breeds was observed.